‘The Cries of Pagan Desperation’: Synge, Riders to the Sea and the discontents of historical time - Collins, Christopher (Carysfort Press, 2014)
This essay considers Synge’s staging of the caoine (keen) in Riders to the Sea(1904). It argues that the caoine in Riders to the Sea is not simply an aesthetic and unethical fetishization of pre-Christian cultural residue predicated on class insecurity, but a performance philosophy of modernity. Synge’s knowledge of caoineadh (keening) as a cultural performance, and as an object of academic study, is contextualized using various unpublished manuscripts in order to demonstrate how the caoine in the Ireland of Synge’s time was considered to be the discontents of historical time. Unorthodox histories summon unorthodox temporalities and, in Riders to the Sea, it is argued that Synge called forth an alternative temporality of modernity that punctured and punctuated dominant specularity whether that was Anglo-Irish or Catholic in its gaze.